Petrographic composition and directional properties of tills on the NW surroundings of the Gdánsk Bay, Nothern Poland - Woźniak, Piotr Paweł; Czubla, Piotr; Wysiecka, Graźyna; Drapella, Małgorzata (Geologija, 2009)
In this paper, the authors focus on some selected lithological properties of tills: petrographic composition of the 5-10 mm fraction, petrographic composition of the coarse fraction ( > 20 mm, analysed by the indicator erratics method) and the long axis orientation of clasts. As the study area the authors chose a territory located in Northern Poland on the NW surroundings of the Gdańsk Bay - between Puck and Lake Žarnowieckie. It was found that during the Last Glaciiation the study region was fed mainly from the territory of Sweden, middle and south-eastern Sweden in particular. There existed, in parallel with the dominant (in the study region) NNW ice-sheet advance direction, also another, local ice-sheet advance route manifested in the east, which deposited a till bed in the neighbourhood of Puck.